Aquatic Toxicology and Hazard Assessment 1981
DOI: 10.1520/stp34156s
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and Chronic Toxicity of Bis(tributyltin) Oxide (TBTO): Tests with a Saltwater Fish

Abstract: The accumulation and depuration of bis(tributyltin) oxide (TBTO), a widely used active ingredient in antifouling paints, and its acute and chronic toxicity to sheepshead minnows (Cyprinodon variegatus) were determined. Equilibrium between the concentration of carbon-14-labeled-TBTO in seawater and in fish tissues was not reached after 58 days of exposure. The maximum observed bioconcentration factor in whole fish was ×2600. The maximum observed bioconcentration factors for the muscle, viscera, and remains were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(24 citation statements)
references
References 5 publications
1
22
0
1
Order By: Relevance
“…A portion of the surficial layer (1 cm) of the sediment was removed with a spatula, at about the mid-tide level, placed in a polyethylene bag and deep frozen (-20°C) for storage. Homogenised wet unsieved sub-samples were analysed for TBT following the methods based on Ward et al (1981) that are fully described by Bryan et al (1986), rendering a detection limit of about 5 ng Sn g -1 dry weight (DW). The moisture content was determined from a separate aliquot.…”
Section: Methodsmentioning
confidence: 99%
“…A portion of the surficial layer (1 cm) of the sediment was removed with a spatula, at about the mid-tide level, placed in a polyethylene bag and deep frozen (-20°C) for storage. Homogenised wet unsieved sub-samples were analysed for TBT following the methods based on Ward et al (1981) that are fully described by Bryan et al (1986), rendering a detection limit of about 5 ng Sn g -1 dry weight (DW). The moisture content was determined from a separate aliquot.…”
Section: Methodsmentioning
confidence: 99%
“…Although this technique does not perform the complete OTs speciation (of butyl-, phenyl-and octyltins), previous studies have shown that butyltins (BTs) represent the dominant OT fraction in the study area and, of these, TBT is the most abundant compound. [19][20][21] Analytical procedures were largely based on those of Ward et al 22 as modified and described fully by Bryan et al 8 Recoveries of TBT and DBT were $100 and 92% respectively, and were corrected by the use of standard additions in all samples. Detection limits for TBT and DBT were about 10 ng Sn g À1 dw.…”
Section: Female Ot Body Burdensmentioning
confidence: 99%
“…The samples collected in 1997 were analysed for TBT and dibutyltin (DBT) using methods described in detail elsewhere. 11,12 Briefly, four to six frozen specimens (separated by sex) were pooled and then homogenized. Two replicates of tissues were taken for analysis.…”
Section: Organotinsmentioning
confidence: 99%